A preliminary study of the water quality status Along Sungai Mada, Kodiang, Kedah To The Sungai Baru Estuary, Perlis / Faridah Hanum Hj. Badrun, Zailuddin Ariffin and Baharuddin Salleh - Hj. Badrun, Faridah Hanum; Ariffin, Zailuddin; Salleh, Baharuddin (Universiti Teknologi MARA, Perlis, 2003)
A preliminary study was carried out to determine the water quality status along the Sungai Mada irrigation channel at Kodiang, Kedah to the Sungai Baru estuary at Kuala Perils. Nine stations were identified, namely Sg. Mada-Titi Kodiang (SIJ, Sg. Mada-Kg Sena (S2j , Sg.. Mada-Guar Sanji (S3), Long Boh (S4), Utan Aji (S5), Pekan Simpang Empat (S6), Simpang Empat road bridge (S7), Sungai Baru floodgate (S8) and Sungai Baru road bridge (S9). The parameters studied were temperature, dissolved oxygen (DO), salinity, total dissolved solids (TDS), pH and specific conductance (SpC). All these parameters were measured at a depth of about 1.0 m from the water surface. Both temperature and DO parameters generally show results which reflect the time of sampling. Results for pH, salinity, TDS and SpC show some degree of water quality degradation starting from S7 through the estuary end at S9. Measurements from salinity, TDS, pH and SpC parameters also suggest salt water intrusion to about 3.5 km inland from the Sungai Baru estuary.